2015
DOI: 10.1103/physrevd.91.054037
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of charmed pentaquarks

Abstract: In this work, we explore the charmed pentaquarks, where the relativistic five-quark equations are obtained by the dispersion relation technique. By solving these equations with the method based on the extraction of the leading singularities of the amplitudes, we predict the mass spectrum of charmed pentaquarks with $J^P=1/2^{\pm}$ and $3/2^{\pm}$, which is valuable to further experimental study of charmed pentaquark.Comment: 10 pages, 4 figures and 4 tables. Accepted by PRD. arXiv admin note: substantial tex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…However some experimental searches on pentaquarks still came into view with null results such as the result of ALICE Collaboration investigating φ(1869) pentaquark [64] and J-PARC E19 Collaboration searching for Θ + [65] state. On the other hand the theoretical studies indicated that the search on the pentaquark containing heavy quark constituents is still necessary [66] due to the effect of such a structure on the stability of the hadronic structures beyond the traditional hadrons [67]. In 2015 the observation of two pentaquark states, P + c (4380) and P + c (4450), was finally reported by LHCb Collaboration in the Λ 0 b → J/ψK − p decays.…”
Section: Introductionmentioning
confidence: 99%
“…However some experimental searches on pentaquarks still came into view with null results such as the result of ALICE Collaboration investigating φ(1869) pentaquark [64] and J-PARC E19 Collaboration searching for Θ + [65] state. On the other hand the theoretical studies indicated that the search on the pentaquark containing heavy quark constituents is still necessary [66] due to the effect of such a structure on the stability of the hadronic structures beyond the traditional hadrons [67]. In 2015 the observation of two pentaquark states, P + c (4380) and P + c (4450), was finally reported by LHCb Collaboration in the Λ 0 b → J/ψK − p decays.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013 with the observation of Z c [30], being an indication for the existence of pentaquark, the attentions have centered upon pentaquarks again. While there still were some null results coming from experimental researches such as the results of ALICE Collaboration investigating φ(1869) pentaquark [31] and J-PARC E19 Collaboration searching for Θ + [32], the theoretical studies were indicating necessity for searching the pentaquark states with heavy quark contents [33]. Finally there came the long sought result from the LHCb Collaboration with the announcement of the observation of P + c (4380) and P + c (4450), in the Λ 0 b → J/ψK − p decay with masses 4380 ± 8 ± 29 MeV and 4449.8 ± 1.7 ± 2.5 MeV, spins 3/2 and 5/2 and decay widths 205 ± 18 ± 86 MeV and 39 ± 5 ± 19 MeV, respectively [1].…”
mentioning
confidence: 99%
“…Mesonbaryon molecules have been suggested in [22][23][24][25][26][27][28][29][30]. Pentaquark states of diquark-diquark-antiquark nature have been suggested in [31][32][33][34][35], compact diquark-triquark pentaquarks in [36,37],D-soliton states in [38], genuine multiquark states in [39,40], and some papers have suggested that the peaks could be related to kinematic effects of a triangle singularity [41][42][43]. Summaries of the theoretical and experimental work done can be seen in Refs.…”
Section: Introductionmentioning
confidence: 99%